Coronary computed tomographic angiography in coronary artery bypass grafts: Comparison between low-concentration Iodixanol 270 and Iohexol 350 - Wang, H.; Xu, L.; Zhang, N.; Fan, Z.; Zhang, Z.; Sun, Zhonghua (LWW Business Offices, 2014)
Objective: The aim of this study was to evaluate the feasibility of low concentration iso-osmolar Iodixanol 270 compared with Iohexol 350 in patients with coronary artery bypass grafts (CABG) undergoing coronary CT angiography (CCTA). Methods: A total of 80 consecutive patients undergoing CABG follow up with the use of CCTA were prospectively enrolled, with 40 patients assigned to Iodixanol 270 and 40 patients to Iohexol 350.. In both groups, contrast medium was injected at an injection rate of 4.5 mL/s in patients with BMI>24 kg/m2 and 3.5 mL/s in patients with BMI≤24 kg/m2. Image quality score and visualization of bypass grafts were evaluated. Subjective assessment of image quality for each coronary artery segment was determined using a 4-point grading scale by two reviewers, while objective evaluation of image quality was conducted by measuring the mean CT attenuation values (HU) in terms of standard deviation (SD), contrast-to noise ratio (CNR), and signal-to-noise ratio (SNR) in the ascending aorta. Results: The mean contrast volume for Iodixanol 270 and Iohexol 350 group was 66.28 ± 12.00 ml, and 64.98 ± 12 ml, respectively with no significant difference (p=0.57). The mean CT attenuation value in the 270-group was 409.69±98.27, which was lower than in the 350-group, which was 475.14±104.75 (p=0.04). The subjective image quality for 270-group was superior to 350-group in the arterial graft vessels (p=0.027), while there was no significant difference between the two groups in the venous graft vessels (p=0.377). There was no significant difference in terms of SDAO, SNR, and CNR between the two groups. Conclusion: Low concentration iso-osmolar Iodixanol 270 provides image quality comparable to Iohexol 350, allowing diagnostic CCTA follow-up of patients with CABG.